2020
DOI: 10.1123/ijsnem.2019-0193
|View full text |Cite
|
Sign up to set email alerts
|

Professional Female Athletes Are at a Heightened Risk of Iron-Deficient Erythropoiesis Compared With Nonathletes

Abstract: This study primarily aimed to quantify and compare iron status in professional female athletes and nonathletes. Furthermore, this study also aimed to identify differences in iron status according to sporting discipline and explore the relationship between ferritin concentration and weekly training volume in professional athletes. A total of 152 participants were included in this study, including 85 athletes who were members of senior teams (handball, n = 24; volleyball, n = 36; soccer, n = 19; and judo, n = 6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…Higher iron supplement use was found among those players training more hours in the gym per week. The prevalence of iron deficiency among females athletes from team sports, 24 and elite female football players in particular 25 is high, so supplementation can be justified. Also, menstruating females, mainly those with heavy menstrual bleeding, are at elevated risk for iron deficiency 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Higher iron supplement use was found among those players training more hours in the gym per week. The prevalence of iron deficiency among females athletes from team sports, 24 and elite female football players in particular 25 is high, so supplementation can be justified. Also, menstruating females, mainly those with heavy menstrual bleeding, are at elevated risk for iron deficiency 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is a serious problem among athletes ( McCormick et al, 2020 ). The prevalence rates of IDA in professional and elite athletes were reported to be 2–29% and 3–7% in women ( Landahl et al, 2005 ; Ponorac et al, 2020 ) and men ( Clement et al, 1987 ; Dubnov & Constantini, 2004 ), respectively. The primary mechanisms by which sports lead to ID are increased iron loss and blockage of iron absorption due to hepcidin bursts ( Clenin et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated the beneficial effects of iron administration for the treatment of chronic heart failure and ID, even in the absence of anemia ( Anker et al, 2009 ; Okonko et al, 2008 ). The prevalence rates of ID were reported to be 49–52% in female professional athletes ( Nabhan et al, 2020 ; Ponorac et al, 2020 ), and 2.9–15% in male college or elite athletes ( Nabhan et al, 2020 ; Parks, Hetzel & Brooks, 2017 ). Some researchers have attempted to provide iron supplements in athletes without anemia to improve their athletic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The distortion of physiological homeostasis and increase of ionized iron concentration in the bloodstream due to intense exercise, which is a consequence of this process, on the one hand, may contribute to the intensification of free radical reactions [ 4 ] and contribute to the increase in inflammation and disturbances in iron metabolism, on the other hand. Research shows that female athletes, compared to their male peers who do not practice sports, are more likely to suffer from disturbances in iron homeostasis in their bodies [ 5 , 6 ]. Moreover, the post-exercise changes in parameters related to iron metabolism may result in an increased frequency of pathogenic infections in female athletes and a decrease in their ability to perform intense exercise [ 7 ].…”
Section: Introductionmentioning
confidence: 99%